Hemophagocytic lymphohistiocytosis in patients with inflammatory bowel diseases: a systematic review - Lan, Tingwei; Luo, Qinhuan; Guo, Xiaojuan; Jiang, Xuan (Frontiers in Immunology, 2025)
IntroductionHemophagocytic lymphohistiocytosis (HLH) is a rare but life-threatening hyperinflammatory syndrome. Patients with inflammatory bowel diseases (IBD) appear to be at increased risk of developing HLH, potentially due to immunosuppressive therapies. However, the epidemiology, clinical characteristics, management strategies, and outcomes of HLH in this population remain poorly understood.MethodsWe conducted a systematic review of the literature using PubMed, Web of Science, and Embase. A total of 97 secondary HLH (sHLH) cases and 18 HLH cases with genetic mutations were identified in IBD patients.ResultsAmong IBD patients, sHLH predominantly affected males with Crohn’s disease, with a median age of 33.5 years and a median disease duration of 4 years. Most patients were on thiopurines for IBD management and were in clinical remission at sHLH onset. The most common triggers were infections (particularly CMV and EBV), followed by lymphoma. The overall survival rate for sHLH was 62.5%. Most patients successfully resumed IBD maintenance therapy within 5 months after the sHLH episode, with minimal complications and rare recurrence of IBD or HLH. Older age, lymphoma-induced HLH, and lack of biologic or thiopurine therapy were potential factors associated with mortality. Compared to sHLH, primary HLH patients were younger, more frequently male, predominantly had Crohn’s disease, were less likely to be in remission despite biologic therapy, and had better outcomes with hematopoietic stem cell transplantation (HSCT).DiscussionThis study provides a comprehensive characterization of HLH in IBD patients, offering valuable insights to guide future research aimed at improving clinical outcomes in this unique population.Systematic Review Registrationosf.io identifier, 10.17605/OSF.IO/5GY3E.